A Continuum of Funding Models for OER?: K-State's Open/Alternative Textbook Initiative - Jackson, Carolyn S. (My University, 2026)
Awareness and adoption of OER continues to grow across educational institutions but ensuring long-term sustainability remains a critical challenge as materials that are ostensibly free to use require major investments of time and resources by the creators. The most common funding strategies include government grants, philanthropic support, and institutional investment, where up-front production costs are wholly absorbed to create cost savings for students. But some schools have begun asking students to pay a small fee for courses using open materials to defray the costs of development and maintenance. Some OER projects adopt a freemium model, offering basic content for free while charging for enhanced services like online or print-on-demand components. Still others have moved toward low-cost commercial platforms that require students to pay for access to materials but intentionally keep the price as low as possible. What does this mean for the future? Does asking students to pay a nominal amount for course materials undermine the OER movement or does it provide an alternative financial model that we should all consider? Panel members included: Carolyn Jackson, Kansas State University Patricia Kyle, University of Texas at Austin Amy Rossomondo, University of Kansas
Keywords: Open Educational Resources; OER Sustainibility